In an Adult Horse With Severe Asthma (Previously Recurrent Airway Obstruction) Does Using Inhaled Corticosteroids Result in an Equal Improvement in Clinical Signs When Compared to Systemic Corticosteroids? - Jocelyn, Natasha A (Veterinary Evidence, 2018)
PICO question In an adult horse with severe asthma (previously recurrent airway obstruction (RAO)) does using inhaled corticosteroids result in an equal improvement in clinical signs when compared to systemic corticosteroids? Clinical bottom line The level of confidence in the outcomes from the body of evidence in the 4 papers identified is high. This suggests inhaled corticosteroids (fluticasone and beclomethasone) when used at an appropriate dose can have equivalent effects on severe equine asthma as systemic intravenous dexamethasone. Inhaled corticosteroids can take longer to have the desired effects.